2012
DOI: 10.1139/b2012-016
|View full text |Cite
|
Sign up to set email alerts
|

Sex-ratio variation and the function of staminodes inAralia nudicaulis1This article is part of a Special Issue entitled “Pollination biology research in Canada: Perspectives on a mutualism at different scales”.

Abstract: Aralia nudicaulis L. is a clonal dioecious herb common to forested ecosystems in eastern North America. Across 15 sites, the frequency of female ramets ranged between 5% and 95%. This variation was used to examine hypotheses involving the life history and pollination biology of A. nudicaulis. Because female reproductive function is thought to incur greater resource costs than male function, we predicted that female ramets should (i) be more common where resources (and light in particular) are more abundant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Despite not participating in the production of gametophytes, vestigial and sterile reproductive organs may still participate in reproduction, e.g. staminodes attracting pollinators in mimosoid legumes and other plants (Nicholls and Dorken 2012). Staminodes and pistillodes may be very small, and in these cases, just recording their presence (or absence) may be sufficient.…”
Section: Morphologymentioning
confidence: 99%
“…Despite not participating in the production of gametophytes, vestigial and sterile reproductive organs may still participate in reproduction, e.g. staminodes attracting pollinators in mimosoid legumes and other plants (Nicholls and Dorken 2012). Staminodes and pistillodes may be very small, and in these cases, just recording their presence (or absence) may be sufficient.…”
Section: Morphologymentioning
confidence: 99%
“…In the Scrophulariaceae s.str., approximately 30 % of the genera possess a staminode (e.g., Scrophularia). However, there are very few experimental studies on functional diversification of the staminode in asterids (Walker-Larsen and Harder 2001;Cabrera 2001, 2002;Hawk and Tepedino 2007 in Penstemon; Vieira et al 1992;Bittencourt and Semir 2006;Yanagizawa and Maimoni-Rodella 2007;Guimarães et al 2008;Maués et al 2008; Alves et al 2010 in Jacaranda;Nicholls and Dorken 2012 in Aralia nudicaulis) and none in the family Scrophulariaceae s.str. These cited studies reported different functions for the staminode, which are generally related to pollination (e.g., visual orientation, smell guiding, mediate pollinator contact with reproductive organs, guide to reach the anthers, secondary pollen presentation, visual indicator of flower senescence, and avoidance of pollen robbing).…”
Section: Introductionmentioning
confidence: 99%